A unified materials approach to mitigating optical nonlinearities in optical fiber. II. A. Material additivity models and basic glass properties. (11th December 2017) - Dragic, Peter D.; Cavillon, Maxime; Ballato, Arthur; Ballato, John
Abstract: The purpose of this paper, Part IIA in the trilogy ( Int J Appl Glass Sci . 2018;9:263‐277; Int J Appl Glass Sci . 2018 (in press); Int J Appl Glass Sci . 2018 (in press)), is to describe the continuum models employed to deduce the physical, acoustic, and optical properties of optical fibers that exhibit intrinsically low optical nonlinearities. The continuum models described herein are based on the additivity approaches of Winklemann and Schott (W‐S). Initially developed over 120 years ago, W‐S additivity works well for predicting the basic properties of bulk silicate glasses. While high‐silica‐content glasses are still the gold‐standard for telecommunication and high energy laser fibers, the models have been systematically expanded to include deduction of the physical, thermophysical, and acoustic constants and coefficients that bear on parasitic nonlinearities. The state‐of‐the‐art in W‐S‐based continuum materials models is reviewed here with specific examples provided based on canonical material systems suggested from the findings of Part I and treated in detail in Part III.